(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article analyzes the impact of climate change on forest ecosystems in Armenia. Historical and projected climate data were studied, and the impact of changes in temperature and precipitation on forest distribution, species composition and biodiversity was assessed. The article also presents climate change maps and vulnerability analysis of forest areas. Mitigation and adaptation strategies are proposed, including the use of drought-tolerant species, fire and pest management systems, and conservation of genetic resources. The article also emphasizes the need for a systemic and localized approach to forest policy development and biodiversity conservation.